Immigration, neoconservatism and neoliberalism: The new Canadian citizenship regime in the light of European trajectories - Mathieu Forcier; Frédérick Guillaume Dufour (Cogent Social Sciences, 2016)
A vast range of recent academic scholarships seek to theorize the recent convergence of neoliberal, anti-immigration, xenophobic and populist measures and practices since the Crisis of 2008. This paper analyses recent changes to the Canadian citizenship regime and it compares this changes to neoliberal and neoconservative trends in Europe. The authors argue that although it did not explicitly renounce its pluralistic orientation, the Canadian Conservative Party had already started its neoliberal and neoconservative reorientation of the Citizenship in Canada prior to the Crisis of 2008. Despite several similarities with European trajectories, the Conservative Party needs to deal with structural factors that are specific to the Canadian context: the electoral system; demographic trends; and a public opinion which, unlike in Europe, remains optimistic with regards to the economic contribution of immigration.